Relação entre performance e as 4 fases de confiabilização - Trevisan, Marcos Aurelio (2012)
After many years of stability, the global automotive market undergoes transformations. Traditional manufacturers suffer financial crises in saturated markets, Asian manufacturers expand their market share, the BRICS countries, with market potential will become part of the strategy of the leading manufacturers. For companies to be able to remain inserted in a market like this, means producing at the lowest cost with the best quality in the shortest time, i.e. at the highest level of performance. This level of performance is not easily achieved; need dedication, focus on results and a lot of strategic vision. This paper presents the relationship between the performance of the production and application of the four phases of reliability in a manufacturing system. Sector machining company case study, during the year 2011 has gone through some turmoil, its results were not better than those of competitors, mainly due to the high cost of interruptions to the operation of the machines. These shutdowns caused excessive overtime for production late replacement, rework parts due to the lack of quality, and high cost for corrective maintenance of machines. As a result and discussion has been found that there is not a direct relationship between increasing the total availability of flexible lines and results of performance.